The Presence of Anti-Lactoferrin Antibodies in a Subgroup of Eosinophilic Granulomatosis with Polyangiitis Patients and Their Possible Contribution to Enhancement of Neutrophil Extracellular Trap Formation - Shida, Haruki; Nakazawa, Daigo; Tateyama, Yu; Miyoshi, Arina; Kusunoki, Yoshihiro; Hattanda, Fumihiko; Masuda, Sakiko; Tomaru, Utano; Kawakami, Tamihiro; Atsumi, Tatsuya; Ishizu, Akihiro (Frontiers in Immunology, 2016)
Lactoferrin (Lf) is one of the antigens of anti-neutrophil cytoplasmic antibodies (ANCA) and functions as an endogenous suppressor of neutrophil extracellular trap (NET) formation. However, the prevalence and pathogenicity of anti-lactoferrin antibodies (aLf) in ANCA-associated vasculitis (AAV) remain unrevealed. This study aimed to examine the significance of aLf in AAV, initially. Sixty-five sera from AAV patients, including 41 microscopic polyangiitis (MPA), 5 granulomatosis with polyangiitis (GPA), and 19 eosinophilic granulomatosis with polyangiitis (EGPA) patients, were subjected to aLf detection using enzyme-linked immunosorbent assay. Clinical characteristics were compared between aLf-positive and aLf-negative patients. Neutrophils from healthy donors were exposed to suboptimal dose (10 nM) of phorbol myristate acetate (PMA) with aLf followed by evaluation of NET formation. Results demonstrated that four out of 65 AAV sera (6.2%) were positive for aLf. All of them were EGPA sera (4/19, 21.1%). In EGPA, the frequency of renal involvement, serum CRP levels, and Birmingham Vasculitis Activity Score (BVAS) in the aLf-positive patients were significantly higher than those in the aLf-negative patients, and the aLf titer correlated positively with the serum CRP level and BVAS. The NET formation was particularly enhanced by combined stimulation of 10 nM PMA and 1 µg/mL aLf. IgG isolated from sera of the aLf-positive EGPA patients (250 µg/mL) enhanced NET formation induced by 10 nM of PMA, and the effect was abolished completely by absorption of the aLf. This pilot study suggests that aLf enhance NET formation induced by PMA and are associated with disease activity of EGPA.